Exploring childhood adversity, impulsivity, and cognitive functioning within forensic populations - Johnson, Oliver (2025)
Empirical research has reported associations between childhood adversity and impulsivity, childhood adversity and cognitive functioning, and cognitive functioning and impulsivity in adults; however, the relationship between these factors is more widely evidenced within the general population, than forensic populations. Further exploration regarding how these factors relate among forensic samples may inform psychological formulation and interventions for individuals who disproportionately experience adversity from a young age. This thesis presents four separate studies. Firstly, a systematic review of 11 studies totalling 7,259 participants, provided evidence of the relationship between childhood adversity and trait impulsivity within forensic populations. Secondly, an applied empirical study showed that self-reported childhood adversity predicted difficulties with inhibitory control and cognitive flexibility on a test of executive functioning, within a small adult forensic mental health sample. Thirdly, a research case study was conducted, involving an in-depth exploration of childhood adversity, impulsivity, and cognitive functioning for an individual undergoing treatment in a forensic mental service, wherein a case formulation was developed using various psychometric assessment outcomes, incident data, and collateral information. Finally, a critique of the Childhood Trauma Questionnaire-Short Form (CTQ-SF) in the context of forensic populations found strong evidence of construct validity and internal consistency, whilst other psychometric properties required examination. This thesis provides preliminary evidence of an association between childhood adversity, impulsivity, and cognitive functioning within forensic populations, which has potential implications for forensic practice and research; however, further investigation is required.